SINKRONISASI PERATURAN HUKUM INTERNASIONAL DENGAN HUKUM NASIONAL DALAM UPAYA PENEGAKAN HUKUM ILLEGAL FISHING TERHADAP KAPAL NELAYAN ASING DI ZEE INDONESIA - MUHAMAD RAFLI NIM. A1011191092 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractThis study will discuss whether the enforcement of illegal fishing laws against foreign fishing vessels in Indonesia's ZEE carried out by the Indonesian government is in accordance with Article 73 Paragraph (3) of the 1982 United Nations Conventions on the Law of the Sea (UNCLOS) and what legal efforts can be made by the Indonesian government to synchronize international law and national law to be more appropriate. This study aims to analyze whether the enforcement of illegal fishing laws against foreign fishing vessels in Indonesia's ZEE carried out by the Indonesian government is in accordance with Article 73 Paragraph (3) of the United Nations Conventions on the Law of the Sea (UNCLOS) 1982 and to analyze what legal efforts can be made by the Indonesian government to synchronize international law and national law to be more appropriate.The type of research used in this study is normative legal research. The type of approach used to analyze and obtain results is the type of statutory approach (statute approach). The data sources used are secondary data with legal materials used, among others: primary, secondary, and tertiary legal materials. The data collection techniques used are Literature Studies and Interviews. And the data analysis technique used is a Qualitative analysis technique.The results of this study show that law enforcement of illegal fishing against foreign fishing vessels in Indonesia's ZEE from 2019 to 2022 is in accordance with Article 73 Paragraph (3) of the United Nations Conventions on the Law of the Sea (UNCLOS) 1982. And, there are several legal efforts that can be made by the Indonesian government to synchronize international law and national law to make it more appropriate, namely by amending the Fisheries Law to conform to the 1982 United Nations Conventions on the Law of the Sea (UNCLOS), making bilateral agreements with the countries concerned, and suggesting changes to the contents of the 1982 United Nations Conventions on the Law of the Sea (UNCLOS) to countries. It can be noted that the enforcement of illegal fishing laws in Indonesia's ZEE is in accordance with Article 73 Paragraph (3) of the United Nations Conventions on the Law of the Sea (UNCLOS) 1982, but there is still another problem, namely that the accused foreign fishermen are unable to pay the fines imposed on him and they shall not be subject to imprisonment if there is no agreement to the contrary between the states concerned. Thus, law enforcement carried out by the Indonesian government cannot be carried out properly. Keywords: Synchronization, Law enforcement, Illegal Fishing, United Nations Conventions on the Law of the Sea 1982, Fisheries Law, Exclusive economic zone. AbstrakPenelitian ini akan membahas mengenai apakah penegakan hukum illegal fishing terhadap kapal nelayan asing di ZEE Indonesia yang dilakukan oleh pemerintah Indonesia sudah sesuai dengan Pasal 73 Ayat (3) United Nations Conventions on the Law of the Sea (UNCLOS) 1982 dan apa upaya hukum yang dapat dilakukan oleh pemerintah Indonesia untuk mensinkronkan hukum internasional dan hukum nasional agar lebih sesuai. Penelitian ini bertujuan untuk menganalisis apakah penegakan hukum illegal fishing terhadap kapal nelayan asing di ZEE Indonesia yang dilakukan oleh pemerintah Indonesia sudah sesuai dengan Pasal 73 Ayat (3) United Nations Conventions on the Law of the Sea (UNCLOS) 1982 dan untuk menganalisis apa upaya hukum yang dapat dilakukan oleh pemerintah Indonesia untuk mensinkronkan hukum internasional dan hukum nasional agar lebih sesuai.Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian hukum normatif. Jenis pendekatan yang digunakan untuk menganalisis dan memperoleh hasil adalah jenis pendekatan Perundang-Undangan (statute approach). Sumber data yang digunakan adalah data sekunder dengan bahan hukum yang digunakan antara lain: bahan hukum primer, sekunder, dan tersier. Teknik pengumpulan data yang digunakan adalah Studi Pustaka dan Wawancara. Dan teknik analisis data yang digunakan adalah teknik analisis Kualitatif. Hasil penelitian ini menunjukan bahwa penegakan hukum illegal fishing terhadap kapal nelayan asing di ZEE Indonesia sejak tahun 2019 sampai tahun 2022 sudah sesuai dengan Pasal 73 Ayat (3) United Nations Conventions on the Law of the Sea (UNCLOS) 1982. Dan, terdapat beberapa upaya hukum yang dapat dilakukan oleh pemerintah Indonesia untuk mensinkronkan hukum internasional dan hukum nasional agar lebih sesuai, yaitu dengan mengubah Undang-Undang Perikanan untuk disesuaikan dengan United Nations Conventions on the Law of the Sea (UNCLOS) 1982, membuat perjanjian bilateral dengan negara-negara yang bersangkutan, dan menyarankan perubahan isi United Nations Conventions on the Law of the Sea (UNCLOS) 1982 kepada negara-negara. Dapat diketahui bahwa penegakan hukum illegal fishing di ZEE Indonesia sudah sesuai dengan Pasal 73 Ayat (3) United Nations Conventions on the Law of the Sea (UNCLOS) 1982, tapi masih terdapat permasalahan lain yaitu Terdakwa nelayan asing tidak mampu membayar denda yang dijatuhkan kepadanya dan mereka tidak dapat dikenakan pidana penjara jika tidak ada perjanjian sebaliknya antara negara-negara yang bersangkutan. Dengan demikian, penegakan hukum yang dilakukan oleh pemerintah Indonesia tidak dapat terlaksana dengan baik. Kata Kunci: Sinkronisasi, Penegakan hukum, Illegal Fishing, United Nations Conventions on the Law of the Sea 1982, Undang-Undang Perikanan, Zona ekonomi ekslusif.